Simón del desierto [videorecording (DVD)] - Buñuel, Luis, 1900-1983; Buñuel, Luis, 1900-1983; Brook, Claudio; Pinal, Silvia; Alvarez Félix, Enrique, -1996 (Criterion collection, 2008)
"Tells the story of an early Christian ascetic -- modeled on Saint Simon Stylites -- who has lived atop a pillar, surrounded by a barren landscape, for six years, six months, and six days to prove his devotion to God. But the Devil, in the figure of the beautiful Silvia Pinal, huddles below, trying to tempt him down. A skeptic's vision of religious conviction, Luis Buñuel's short and sweet satire is one of his most renowned works of surrealism"--Container.